2000
DOI: 10.1177/0093854800027005005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Locus of Control and Custody Level on Intake and Prison-Adjustment Depression

Abstract: This study examines differences in initial and later depressive symptoms of 325 male prisoners based on three levels of custody and four levels of locus of control. Results extend previous findings concerning locus of control and prison-intake depression by including a measure of types of custody and later adjustment depression. Significant differences emerged for both groups with high internal and external locus of control orientations. The highly internal group was the least depressed at both testings. High … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
7

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 35 publications
1
16
0
7
Order By: Relevance
“…Further, research has found differences in prison adjustment through emotions, attitudes and behaviors to be a function of either age (MacKenzie, 1987), gender (MacKenzie et al, 1989;Warren, Hurt, Loper, & Chauhan, 2004), or both (Boothby & Durham, 1999). Finally, MacKenzie, Goodstein, and Blouin (1987) and Reitzel and Harju (2000) reveal the importance of inmates' perceived level (or locus) of control over their environment as an important influence on inmates' prison adjustment. Thus, the implication suggested by past research is that there is reason to suspect inmate adjustment to prison, in general, may be contingent on a number of different variables, and that inmates may experience differential adjustment to life in prison due to a variety of individual characteristics.…”
Section: Special Sensitivity To Prison 1093mentioning
confidence: 99%
“…Further, research has found differences in prison adjustment through emotions, attitudes and behaviors to be a function of either age (MacKenzie, 1987), gender (MacKenzie et al, 1989;Warren, Hurt, Loper, & Chauhan, 2004), or both (Boothby & Durham, 1999). Finally, MacKenzie, Goodstein, and Blouin (1987) and Reitzel and Harju (2000) reveal the importance of inmates' perceived level (or locus) of control over their environment as an important influence on inmates' prison adjustment. Thus, the implication suggested by past research is that there is reason to suspect inmate adjustment to prison, in general, may be contingent on a number of different variables, and that inmates may experience differential adjustment to life in prison due to a variety of individual characteristics.…”
Section: Special Sensitivity To Prison 1093mentioning
confidence: 99%
“…Incarcerated offenders are reported to experience a high prevalence of depression and depressive disorders (Reitzel & Harju, 2000). For example, Boothby and Durham (1999) reported that over half (57%) of their sample of 1,494 offenders experienced feelings of depression that fell between the ranges of mild to severe.…”
mentioning
confidence: 99%
“…Sousa, 2007), bem como no estudo de Zamble e Porporino (1988). Estes dados vão ainda ao encontro de estudos que verificaram que a sobrecarga emocional própria da fase inicial da execução da pena se vê esbatida à medida que o recluso de adapta à instituição prisional e que, geralmente os reclusos retomam o seu normal funcionamento depois de reagirem adaptativamente ao impacto da detenção e à fase inicial de reclusão (Cooper, 1974;Elger, 2004;Gonçalves, 2008;Reitzel & Harju, 2000;Ribeiro & Barros, 1995;Zamble & Porporino, 1988). Por outro lado, verifica-se que os reclusos que experienciam ideação suicida continuam normalmente a experiencia-la após seis meses de reclusão.…”
Section: Discussionunclassified